Porous composite, negative electrode and lithium battery including the same, and method for producing the same
A porous complex with nano-pores and graphene matrix addresses the conductivity and stability issues of conventional carbon-based electrodes, enhancing the performance of lithium batteries in high-energy density and fast charging applications.
Patent Information
- Application Number
- JP2023504395
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-07-21
- Filing Date
- 2021-07-20
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2041-07-20
AI Technical Summary
Conventional carbon-based electrode materials for lithium batteries face challenges in achieving high conductivity and stability due to graphene aggregation during manufacturing, limiting their performance in high-energy density and fast charging/discharging applications.
A porous complex is developed, comprising graphene with nano-pores of 50 nm or less, integrated with a graphene matrix, which enhances electronic conductivity and cohesion, improving the cycle characteristics of the electrode.
The porous complex improves the cycle characteristics and high-rate performance of lithium batteries by providing improved electronic conductivity and structural integrity, enhancing their capacity for high-energy density and fast charging/discharging.
Smart Images

Figure 0007623469000004 
Figure 0007623469000005 
Figure 0007623469000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a porous composite, a negative electrode and a lithium battery using the same, and a method for producing the same. [Background technology]
[0002] In order to meet the trend of miniaturization and high performance of various devices, it is becoming important for lithium batteries to have high energy density in addition to miniaturization and weight reduction, i.e., high capacity lithium batteries are becoming important.
[0003] In addition to high energy density, rapid charging and discharging is also important for electric vehicles and energy storage systems (ESS), which means that lithium batteries capable of rapid charging and discharging are becoming increasingly important.
[0004] In order to realize lithium batteries that meet the above-mentioned applications, conductive materials that can provide improved conductivity have been investigated.
[0005] In addition to conventional carbon-based conductive materials, graphene has been considered as an alternative. However, it has been difficult to realize the theoretical physical properties due to the aggregation of graphene during the electrode manufacturing process.
[0006] Therefore, there remains a need for new materials that can provide improved physical properties compared to conventional conductive materials. Summary of the Invention [Problem to be solved by the invention]
[0007] An object of the present invention is to provide a porous composite that provides improved charge / discharge characteristics compared to conventional carbon-based conductive materials.
[0008] Another object of the present invention is to provide a negative electrode including the porous composite.
[0009] Another problem to be solved by the present invention is to provide a lithium battery including the porous composite.
[0010] Another problem to be solved by the present invention is to provide a method for manufacturing the porous composite.
Means for Solving the Problems
[0011] According to one aspect, a porous composite including nanopores and graphene is provided, wherein the nanopores are arranged in a graphene matrix including the graphene, and the size of the nanopores is 50 nm or less.
[0012] According to another aspect, a negative electrode including a negative electrode active material and the porous composite according to the above is provided.
[0013] According to still another aspect, a lithium battery including a positive electrode, a negative electrode, and an electrolyte disposed between the positive electrode and the negative electrode is provided, wherein at least one of the positive electrode and the negative electrode includes the porous composite according to the above.
[0014] According to still another aspect, a method for manufacturing a porous composite is provided, the method including: preparing a composite precursor including silica or a first metal oxide and at least one selected from reaction gases composed of a carbon source gas, and heat-treating the silica or the first metal oxide; and preparing a porous composite by removing at least one selected from silica or the first metal oxide and SiO x (0 < x < 2) or a second metal oxide from the composite precursor. x (0 < x < 2) or a second metal oxide from the composite precursor.
Effects of the Invention
[0015] According to one embodiment, the cycle characteristics of a lithium battery are improved by employing a composite containing nanopores of 50 nm or less and graphene. [Brief description of the drawings]
[0016] [Figure 1A] 1 is a high-resolution transmission electron microscope (HR-TEM) image of the composite precursor prepared in Example 1. [Figure 1B] 1 is a high-resolution transmission electron microscope (HR-TEM) image of the porous composite prepared in Example 1. [Figure 1C] 1 is a high-resolution transmission electron microscope (HR-TEM) image of the porous composite prepared in Example 1. [Figure 1D] 1 is a high-resolution transmission electron microscope (HR-TEM) image of the porous composite prepared in Example 1. [Figure 1E] 1 is a high-resolution transmission electron microscope (HR-TEM) image of the porous composite prepared in Example 1. [Figure 2A] 1 shows X-ray photoelectron spectrum (XPS) images of C 1s orbital of the composites prepared in Example 1, Example 2, and Comparative Example 1. [Figure 2B] 1 shows X-ray photoelectron spectrum (XPS) images of O 1s orbital of the composites prepared in Example 1, Example 2, and Comparative Example 1. [Figure 2C] 1 shows X-ray photoelectron spectrum (XPS) images of Si 2p orbitals of the composites prepared in Example 1, Example 2, and Comparative Example 1. [Diagram 3] 1 is a schematic diagram illustrating a process for forming a porous composite according to an embodiment; [Figure 4] 1 is a schematic diagram of a lithium battery according to an embodiment; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The present inventive concept described below may be modified in various ways and may have various embodiments, but specific embodiments are illustrated in the drawings and described in detail in the detailed description. However, they are not intended to limit the present inventive concept to specific embodiments, and should be understood to include all modifications, equivalents, or alternatives within the technical scope of the present inventive concept.
[0018] The terms used below are merely used to describe specific embodiments and are not intended to limit the present invention. A singular expression includes a plural expression unless the context clearly indicates otherwise. In the following, terms such as "comprise" or "have" indicate the presence of a feature, number, step, operation, component, part, ingredient, material, or combination thereof described in the specification, and should be understood not to preclude the presence or addition of one or more other features, numbers, steps, operations, components, parts, ingredients, materials, or combinations thereof. In the following, " / " can be interpreted as "and" or "or" depending on the context.
[0019] In the drawings, thicknesses are exaggerated or reduced to clearly depict the various layers and regions. Similar parts are designated by the same reference numerals throughout the specification. Throughout the specification, when a part, such as a layer, film, region, or plate, is referred to as being "on" or "above" another part, this includes not only when it is directly on top of the other part, but also when there is another part between them. Throughout the specification, terms such as first and second may be used to describe various components, but the components are not limited by the terms. The terms are used only to distinguish one component from another.
[0020] Hereinafter, the porous composite, the anode and the lithium battery including the same, and the manufacturing method thereof according to example embodiments will be described in more detail.
[0021] The porous composite includes nanopores and graphene, the nanopores being disposed within a graphene matrix including the graphene, and the nanopores having a size of 50 nm or less.
[0022] The porous composite includes graphene, which provides high electronic conductivity. In addition, the porous composite has a porous structure including nanopores with a size of 50 nm or less arranged in a graphene matrix, which provides excellent adhesion to an electrode active material during electrode preparation. Therefore, the cycle characteristics of an electrode including the porous composite are improved.
[0023] The size of the nanopores contained in the porous composite can be calculated, for example, manually from a high resolution transmission electron microscope (HR-TEM) image or automatically by software. Alternatively, the size of the nanopores contained in the porous composite can be measured by nitrogen adsorption. The size of the nanopores is, for example, the diameter of the pore in the case of a spherical pore, and the maximum distance between any two ends of the pore in the case of a non-spherical pore. When a part of the nanopore is surrounded by graphene, the size of the nanopore is twice the radius of curvature of the graphene surrounding the nanopore.
[0024] The graphene may have a grass-like structure, and nanopores may be distributed within the grass-like structure.
[0025] For example, graphene has a branched structure, and nanopores are also distributed within the branched structure of graphene. The branched structure of graphene includes, for example, multiple graphene particles that are in contact with each other. The branched structure of graphene can provide multiple conductive paths.
[0026] The graphene is, for example, a hemispherical structure, and nanopores are distributed within the hemispherical structure. The size of the hemispherical structure is, for example, 50 to 300 nm. The term "hemispherical" includes any shape that is substantially close to a hemisphere. For example, it includes any shape such as a hemisphere or a semi-ellipse. When the structure is hemispherical, the size of the structure is twice the average radius of curvature of the structure. By forming a graphene-spherical structure, the porous composite can be easily bonded to an electrode active material within an electrode.
[0027] The graphene is, for example, a spherical structure, and nanopores are distributed within the spherical structure. The size of the spherical structure is, for example, 50 to 300 nm. The meaning of "spherical" includes any shape that is substantially close to a sphere. For example, it includes any shape such as a sphere and an ellipse. When the structure is spherical, the size of the structure indicates the average particle size of the structure. When the structure is elliptical, it also indicates the major axis diameter range. By forming a hemispherical structure of graphene, the porous composite can be easily impregnated with an electrolyte.
[0028] Graphene may also have a spiral structure in which a plurality of spherical structures are connected. Nanopores are also distributed within the spherical structures of the spiral structure. The size of the spiral structure is, for example, 500 nm to 100 μm. By forming a spiral structure of graphene, the porous composite can be easily bonded to an electrode active material in an electrode.
[0029] Graphene may also be a cluster structure in which a plurality of spherical structures are aggregated. Nanopores are also distributed within the spherical structures of the cluster structure. The size of the cluster structure is, for example, 0.5 mm to 10 cm. Because graphene has a cluster structure, the porous composite may be easily bonded to an electrode active material in an electrode.
[0030] The porous composite may be, for example, a crumpled structure. The porous composite may be, for example, a faceted-ball structure. The faceted-ball structure may be, for example, a spheroidized structure. Nanopores may be distributed inside the faceted-ball structure. The faceted-ball structure of the porous composite may be easily bonded to an electrode active material in an electrode due to the faceted-ball structure of the porous composite.
[0031] The porous composite may be, for example, a wrinkled planar structure. The wrinkled planar structure may be, for example, a spheroidized structure. Nanopores may be distributed within the wrinkled planar structure. Such a wrinkled planar structure allows the porous composite to be easily bonded to an electrode active material within an electrode.
[0032] In the porous composite, the graphene content is, for example, 90 parts by weight or more, 95 parts by weight or more, 98 parts by weight or more, 99 parts by weight or more, or 99.5 parts by weight or more, based on 100 parts by weight of the total weight of the porous composite. The porous composite may be, for example, composed of graphene.
[0033] Graphene is a polycyclic aromatic molecule in which a number of carbon atoms are covalently linked together to form a six-membered ring as a basic repeating unit, but may also include five-membered and / or seven-membered rings. As a result, graphene can also be viewed as a single layer of carbon atoms covalently bonded together (usually sp2 bonds). Graphene can be composed of a single layer, but multiple single layers can be stacked together to form multiple layers. Graphene can have a number of stacked layers, for example, 1 to 100 layers, 2 to 100 layers, or 3 to 50 layers.
[0034] Graphene has a crystallinity of 0.5 to 1.5, for example, 1.055 to 1.146. The crystallinity of graphene (or the degree of disorder of graphene crystals) can be obtained by measuring the intensity ratio of the D peak and the G peak in the Raman analysis spectrum.
[0035] The graphene contained in the porous composite is extended by a distance of 10 nm or less in the nanopores and also includes at least 1 to 20 layers of graphene layers. For example, by stacking a plurality of graphene layers, graphene having a total thickness of 12 nm or less can be arranged around the nanopores. For example, the total thickness of the graphene is also 0.6 to 12 nm. The graphene layer can surround a part or all of the nanopores. For example, referring to FIGS. 1D and 1E, a plurality of stacked graphene layers have a spherical or hemispherical form and surround a part or all of the periphery of the nanopores.
[0036] The size of the nanopores contained in the porous composite is, for example, 1 to 50 nm, 1 to 40 nm, 1 to 30 nm, 1 to 20 nm, 2 to 20 nm, 5 to 20 nm, or 10 to 20 nm. By including nanopores in such a range in the porous composite, further improved electron conductivity can be provided.
[0037] A plurality of nanopores can be connected to form secondary pores in various forms. The secondary pores formed by connecting a plurality of nanopores are, for example, in the form of nanotubes. The cross-sectional length of the pores in the nanotube form is 500 nm or less, for example, 100 to 300 nm. The diameter of the secondary pores in the nanotube form is about 50 nm or less, for example, 1 to 50 nm.
[0038] The porous composite is, for example, one that further contains one or more selected from silica (SiO 2 ), and SiO which is a reduction product of the silica x (0 < x < 2). Such silica and / or SiO x(0 < x < 2) is not removed during the etching process of the composite precursor containing them and can remain in the nanopores either intentionally or unintentionally. In that case, the porous composite also contains nanopores, silica, and the reduction product of the silica at the same time. The reduction product of silica is, for example, SiO 1.8 SiO 1.9 SiO 1.7 SiO 1.6 SiO 1.5 SiO 1.4 SiO 1.3 and so on.
[0039] The content of silicon (Si) contained in the porous composite is 0.01 to 10 atomic%, 0.01 to 7 atomic%, 0.1 to 5 atomic%, 0.1 to 3 atomic%, or 0.1 to 1 atomic% or less based on the entire porous composite. The content of silicon (Si) contained in the porous composite is also determined by XPS (X-ray photoelectron spectroscopy). The lower the content of silicon (Si) contained in the porous composite, for example, in the charge-discharge process, the reduction of the initial efficiency due to the reaction between the metal and lithium can be prevented.
[0040] The average particle size of silica and SiO x (0 < x < 2), which is the reduction product of the silica, is measured using, for example, a measuring device of the laser diffraction method or the dynamic light scattering method. The average particle size is measured using, for example, a laser scattering particle size distribution meter (for example, LA-920 (manufactured by Horiba, Ltd.)) and is the value of the median particle size (D50) when 50% is accumulated from the primary particle side in volume conversion. One or more of the uniformity deviations selected from silica and SiO x (0 < x < 2), which is the reduction product of the silica, contained in the porous composite is also 3% or less, 2% or less, or 1% or less. The uniformity can be determined, for example, by XPS. Therefore, in the porous composite, one or more selected from silica and SiO x (0 < x < 2), which is the reduction product of the silica, have a deviation of 3% or less, 2% or less, or 1% or less and are uniformly distributed.
[0041] On the other hand, the porous composite may further contain, for example, one or more selected from Group 2 to Group 13, Group 15, and Group 16 of the periodic table of elements, and one or more selected from oxides of the metals. Such metals and / or metal oxides are metals and / or metal oxides that are not removed in the etching process of the composite precursor containing them and remain intentionally or unintentionally in the nano-pores. In that case, the porous composite also contains nano-pores and metals / metal oxides at the same time.
[0042] The porous composite may further contain, for example, one or more selected from a first metal oxide and a second metal oxide which is a reduction product of the first metal oxide.
[0043] The first metal oxide is, for example, one or more represented by the chemical formula M a O b (0 < a ≤ 3, 0 < b ≤ 4, when a is 1, 2, or 3, b is an integer), and the second metal oxide is, for example, one or more represented by the chemical formula M a O c (0 < a ≤ 3, 0 < c < 4, when a is 1, 2, or 3, c is not an integer), and b / a, which is the ratio of a to b of the first metal oxide, may have a larger value than c / a, which is the ratio of a to c of the second metal oxide. M is also one or more metals selected from Group 2 to Group 13, Group 15, and Group 16 of the periodic table of elements.
[0044] The metals contained in the first metal oxide and the second metal oxide are, for example, also one or more selected from Al, Nb, Mg, Sc, Ti, Zr, V, W, Mn, Fe, Co, Pd, Cu, Ag, Zn, Sb, and Se. The first metal oxide is, for example, Al 2 O 3 , NbO, NbO 2 , Nb 2 O 5 , MgO, Sc 2 O 3 , TiO 2 , ZrO2 , V 2 O 3 , WO 2 , MnO 2 , Fe 2 O 3 , Co 3 O 4 , PdO, CuO, AgO, ZnO, Sb 2 O 3 and SeO 2 is selected from among them. The second metal oxide is, for example, Al 2 O z (0 < z < 3), NbO x (0 < x < 2.5), MgO x (0 < x < 1), Sc 2 O z (0 < z < 3), TiO y (0 < y < 2), ZrO y (0 < y < 2), V 2 O z (0 < z < 3), WO y (0 < y < 2), MnO y (0 < y < 2), Fe 2 O z (0 < z < 3), Co 3 O w (0 < w < 4), PdO x (0 < x < 1), CuO x (0 < x < 1), AgO x (0 < x < 1), ZnO x (0 < x < 1), Sb 2 O z (0 < z < 3) and SeO y (0 < y < 2) and is also one or more selected from among them.
[0045] When M is Al, the first metal oxide is, for example, Al 2 O 3 and the second metal oxide is, for example, Al 2 O y (0 < y < 3). The second metal oxide is, for example, Al 2 O 2.9 , Al 2 O 2.8 , Al 2 O 2.7 , Al 2 O2.6 , Al 2 O 2.5 , Al 2 O 2.3 , Al 2 O 2.1 And so on.
[0046] In the porous composite containing the first metal oxide and / or the second metal oxide, the metal contained in the metal oxide is chemically bound to graphene via a chemical bond. The carbon atom (C) of graphene and the metal (M) of the metal oxide are chemically bound, for example, via a COM bond (e.g., a CO-Si bond) via an oxygen atom. The graphene contained in the porous composite is chemically bound to the metal of the metal oxide via a chemical bond, thereby forming a composite of graphene and the metal oxide. Therefore, it is distinguished from a simple physical mixture of graphene and a metal oxide.
[0047] The metal content of the porous composite is 0.01 to 10 atomic %, 0.01 to 7 atomic %, 0.1 to 5 atomic %, 0.1 to 3 atomic %, or 0.1 to 1 atomic % based on the entire porous composite. The metal content of the porous composite can be determined by XPS spectrum. The lower the metal content of the porous composite, the more it can prevent the initial efficiency from decreasing due to the reaction between the metal and lithium during charging and discharging.
[0048] The average particle size of the first metal oxide and the second metal oxide is measured, for example, using a measuring device of a laser diffraction method or a dynamic light scattering method. The average particle size is measured, for example, using a laser scattering particle size distribution meter (for example, LA-920 (manufactured by Horiba, Ltd.)) and is the value of the median particle size (D50) when 50% is accumulated from the elementary particle side in volume conversion. The uniformity deviation of one or more selected from the first metal oxide and the second metal oxide contained in the porous composite is 3% or less, 2% or less, or 1% or less. The uniformity can be determined, for example, by XPS. Therefore, in the porous composite, one or more selected from the first metal oxide and the second metal oxide are uniformly distributed with a deviation of 3% or less, 2% or less, or 1% or less.
[0049] According to another embodiment, a negative electrode includes a negative electrode active material and the porous composite. The negative electrode includes the porous composite, and thus provides improved cycle characteristics.
[0050] The negative electrode active material may be, for example, one or more metals selected from the group consisting of Si, Sn, Al, Ge, Pb, Zn, Ag, and Au, such as a metal capable of being alloyed with lithium, an alloy of a metal capable of being alloyed with lithium, an oxide of a metal capable of being alloyed with lithium, a nitride of a metal capable of being alloyed with lithium, an oxynitride of a metal capable of being alloyed with lithium, a carbide of a metal capable of being alloyed with lithium, or a composite of a metal capable of being alloyed with lithium and a carbon-based material. The carbon-based material may be, but is not limited to, flake graphite, crystalline graphite, amorphous graphite, artificial graphite, carbonaceous mesophase spheres, coke, carbon nanotubes, carbon nanofibers, graphene, graphene oxide, etc., and may be any material that can be used as a carbon-based material in the technical field.
[0051] The negative electrode active material may include, for example, one or more selected from silicon, silicon alloy, silicon nitride, silicon oxynitride, silicon carbide, and silicon-carbon composite. For example, the silicon-carbon composite may be a silicon-carbon nanocomposite. The silicon-carbon nanocomposite means a composite in which one or more of silicon and carbon have a nano-level size of less than 1 μm. For example, the silicon-carbon nanocomposite may be a composite in which silicon nanoparticles and carbon nanoparticles are combined.
[0052] The negative electrode active material may, for example, have a core including a composite particle of silicon and carbon, and a carbon-based coating layer disposed on the surface of the composite particle. The carbon-based coating layer may include amorphous carbon. For example, the carbon included in the coating layer may be a calcined product of a carbon precursor. The carbon precursor may be any one that can be used in the art and that can be calcined to obtain a carbon-based material. For example, the carbon precursor may be one or more selected from the group consisting of polymers, coal tar pitch, petroleum pitch, mesophase pitch, coke, low molecular weight medium oil, coal-based pitch, and derivatives thereof. The carbon-based coating layer is formed on the core to form a solid electrolyte interface (SEI), and Li + The selective passage of ions can prevent silicon from coming into contact with an electrolyte, etc. The content of the coating layer is not particularly limited, and may be more than 0 to 10 wt% based on the total weight of the core. For example, the content of the coating layer may be 1 wt% to 8 wt% based on the total weight of the core including the coating layer. For example, the content of the coating layer may be 1 wt% to 6 wt% based on the total weight of the core including the coating layer. For example, the content of the coating layer may be 1 wt% to 4 wt% based on the total weight of the core including the coating layer.
[0053] The negative electrode active material may be, for example, a carbon-based material. The carbon-based material may be, for example, crystalline carbon, amorphous carbon, or a mixture thereof. The crystalline carbon may be, for example, graphite, such as amorphous, plate-like, flake, spherical, or fibrous natural graphite or artificial graphite. The amorphous carbon may be, for example, soft carbon (low-temperature calcined carbon) or hard carbon, mesophase pitch carbide, calcined coke, etc.
[0054] The negative electrode can be produced, for example, by the following exemplary method, but is not limited to such a method and can be adjusted according to required conditions.
[0055] First, the porous composite, the negative active material, a binder, and a solvent are mixed to prepare a negative active material composition. The prepared negative active material composition is directly coated on a copper current collector and dried to manufacture a negative electrode plate having a negative active material layer. Alternatively, the negative active material composition is cast on a separate support and then peeled off from the support to obtain a film, which is then laminated on the copper current collector to manufacture a negative electrode plate having a negative active material layer.
[0056] The negative electrode current collector is generally made to a thickness of 3 to 500 μm. Such a negative electrode current collector is not particularly limited as long as it is conductive without inducing a chemical change in the battery, and for example, copper, stainless steel, aluminum, nickel, titanium, heat-treated carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. In addition, like the positive electrode current collector, fine irregularities can be formed on the surface to strengthen the binding force of the negative electrode active material, and it can be used in various forms such as a film, sheet, foil, net, porous body, foam, and nonwoven fabric.
[0057] Examples of binders that can be used include vinylidene fluoride / hexafluoropropylene copolymer, polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polytetrafluoroethylene (PTFE), mixtures of the aforementioned polymers, styrene-butadiene rubber-based polymers, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyethylene, polypropylene, ethylene-propylene-diene terpolymer (EPDM), sulfonated EPDM, and fluorine-based rubber. Examples of solvents that can be used include, but are not limited to, N-methylpyrrolidone (NMP), acetone, and water, and any solvent that is used in the relevant technical field can be used.
[0058] It is also possible to further add a plasticizer or pore-forming agent to the negative electrode active material composition to form pores inside the electrode plate.
[0059] The contents of the negative electrode active material, binder, and solvent used in the negative electrode are at levels generally used in lithium batteries. Depending on the application and configuration of the lithium battery, one or more of the binder and the solvent may be omitted.
[0060] The content of the porous composite is, for example, 1 to 10 parts by weight, 1 to 5 parts by weight, or 1 to 3 parts by weight per 100 parts by weight of the negative electrode active material. The content of the binder is, for example, 1 to 20 parts by weight per 100 parts by weight of the negative electrode active material.
[0061] The content of the solvent is, for example, 1 to 50 parts by weight per 100 parts by weight of the negative electrode active material.
[0062] The negative electrode may further include a conventional conductive material in addition to the porous composite. Conventional conductive materials include, but are not limited to, carbon black, graphite particles, natural graphite, artificial graphite, acetylene black, ketjen black, carbon fiber, carbon nanotubes, metal powders, metal fibers or metal tubes, such as copper, nickel, aluminum, and silver, and conductive polymers such as polyphenylene derivatives. Any conductive material may be used as long as it is used as a conductive material in the art.
[0063] According to yet another embodiment, a lithium battery includes a positive electrode, a negative electrode, and an electrolyte disposed between the positive electrode and the negative electrode, at least one of the positive electrode and the negative electrode including the porous composite described above.
[0064] The lithium battery can also be produced, for example, by the following method.
[0065] First, the negative electrode is prepared by the above-mentioned negative electrode manufacturing method.
[0066] Next, a positive electrode active material composition is prepared by mixing a positive electrode active material, a conductive material, a binder, and a solvent. The positive electrode active material composition is directly coated on a metal current collector and dried to manufacture a positive electrode plate. Alternatively, the positive electrode active material composition may be cast on a separate support, and the film peeled off from the support may be laminated on a metal current collector to manufacture a positive electrode plate.
[0067] A part or the whole of the conductive material used in the positive electrode active material may be the porous composite material described above.
[0068] The positive electrode active material may include at least one selected from the group consisting of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, and lithium manganese oxide, but is not necessarily limited thereto, and any positive electrode active material available in the art may be used.
[0069] For example, Li a A 1-b B' b D 2 (wherein, 0.90≦a≦1.8 and 0≦b≦0.5); Li a E 1-b B' b O 2-c D c (wherein, in the formula, 0.90≦a≦1.8, 0≦b≦0.5, and 0≦c≦0.05); LiE 2-b B' b O 4-c D c (wherein, 0≦b≦0.5 and 0≦c≦0.05); Li a Ni 1-b-c Co b B' c D α (wherein, in the formula, 0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05, and 0<α≦2); Li a Ni 1-b-c Co b B' c O 2-α F' α (wherein, in the formula, 0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05, and 0<α<2); Li a Ni 1-b-c Co b B' c O 2-α F' 2 (wherein, in the formula, 0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05, and 0<α<2); Li a Ni 1-b-c Mn b B' c D α (wherein, in the formula, 0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05, and 0<α≦2); Li a Ni 1-b-c Mn b B' c O 2-α F' α (wherein, in the formula, 0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05, and 0<α<2); Li a Ni 1-b-c Mnb B' c O 2-α F' 2 (wherein, in the formula, 0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05, and 0<α<2); Li a Ni b E c G d O 2 (wherein, in the formula, 0.90≦a≦1.8, 0≦b≦0.9, 0≦c≦0.5, and 0.001≦d≦0.1); Li a Ni b Co c Mn d GeO 2 (wherein, in the formula, 0.90≦a≦1.8, 0≦b≦0.9, 0≦c≦0.5, 0≦d≦0.5, and 0.001≦e≦0.1); Li a NiG b O 2 (wherein, in the formula, 0.90≦a≦1.8, 0.001≦b≦0.1); Li a CoG b O 2 (wherein, in the formula, 0.90≦a≦1.8, 0.001≦b≦0.1); Li a MnG b O 2 (wherein, in the formula, 0.90≦a≦1.8, 0.001≦b≦0.1); Li a Mn 2 G b O 4 (wherein, in the above formula, 0.90≦a≦1.8, 0.001≦b≦0.1); QO 2 ;QS 2 ;LiQS 2 ;V 2 O 5 ;LiV 2 O 5 ;LiI'O 2 ;LiNiVO 4 Li 3-f J 2 (PO 4 ) 3 (0≦f≦2);Li 3-f Fe 2 (PO 4 ) 3 (0≦f≦2); LiFePO 4A compound represented by any one of the following chemical formulas can be used.
[0070] In the above chemical formula, A is Ni, Co, Mn, or a combination thereof; B' is Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, a rare earth element, or a combination thereof; D is O, F, S, P, or a combination thereof; E is Co, Mn, or a combination thereof; F' is F, S, P, or a combination thereof; G is Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V, or a combination thereof; Q is Ti, Mo, Mn, or a combination thereof; I' is Cr, V, Fe, Sc, Y, or a combination thereof; and J is V, Cr, Mn, Co, Ni, Cu, or a combination thereof.
[0071] It is also possible to use a compound in which a coating layer is added to the surface of the aforementioned compound, and it is also possible to use a mixture of the aforementioned compound and a compound to which a coating layer is added. The coating layer added to the surface of the aforementioned compound includes, for example, a coating element compound such as an oxide of a coating element, a hydroxide of a coating element, an oxyhydroxide of a coating element, an oxycarbonate of a coating element, or a hydroxycarbonate of a coating element. The compound forming such a coating layer is amorphous or crystalline. The coating element contained in the coating layer is Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr, or a mixture thereof. The method of forming the coating layer is selected within a range that does not adversely affect the physical properties of the positive electrode active material. The coating method is, for example, a spray coating method, a dipping method, etc. Specific coating methods are well known to those skilled in the art, so detailed explanations are omitted.
[0072] For example, LiNiO 2 , LiCoO 2 , LiMn x O 2x(x=1, 2), LiNi 1-x Mn x O 2 (0 <x<1)、LiNi 1-x-y Co x Mn y O 2 (0≦x≦0.5, 0≦y≦0.5), LiNi 1-x-y Co x Al y O 2 (0≦x≦0.5, 0≦y≦0.5), LiFeO 2 , V 2 O 5 , TiS, MoS, etc. may be used.
[0073] The conductive material, binder, and solvent of the positive electrode active material composition may be the same as those of the negative electrode active material composition. Meanwhile, a plasticizer may be further added to the positive electrode active material composition and / or the negative electrode active material composition to form pores inside the electrode plate.
[0074] The contents of the positive electrode active material, conductive material, binder, and solvent are at levels generally used in lithium batteries. Depending on the application and configuration of the lithium battery, one or more of the conductive material, binder, and solvent may be omitted.
[0075] Next, a separator to be inserted between the positive electrode and the negative electrode is prepared. Any separator generally used in lithium batteries may be used. A separator having low resistance to ion movement of the electrolyte and excellent electrolyte wettability may be used. For example, the separator may be selected from glass fiber, polyester, Teflon, polyethylene, polypropylene, polytetrafluoroethylene (PTFE), or a combination thereof, and may be in the form of a nonwoven fabric or a woven fabric. For example, a separator that can be wound such as polyethylene or polypropylene may be used in the lithium ion battery, and a separator having excellent organic electrolyte wettability may be used in the lithium ion polymer battery. For example, the separator may be manufactured by the following method.
[0076] A separator composition is prepared by mixing a polymer resin, a filler, and a solvent. The separator composition may be directly coated on an electrode and dried to form a separator. Alternatively, the separator composition may be cast on a support and dried, and the separator film may be peeled off from the support and laminated on an electrode to form a separator.
[0077] The polymer resin used to manufacture the separator is not particularly limited, and any material that is used as a binder for an electrode plate can be used, such as vinylidene fluoride / hexafluoropropylene copolymer, polyvinylidene fluoride (PVDF), polyacrylonitrile, polymethyl methacrylate, or a mixture thereof.
[0078] Next, the electrolyte is prepared.
[0079] For example, the electrolyte may be an organic electrolyte solution. The electrolyte may also be a solid. For example, the electrolyte may be boron oxide, lithium oxynitride, etc., but is not limited thereto. Any electrolyte that is used as a solid electrolyte in the art may be used. The solid electrolyte may also be formed on the negative electrode by a method such as sputtering.
[0080] For example, an organic electrolyte solution may be prepared by dissolving a lithium salt in an organic solvent.
[0081] The organic solvent may be any that can be used as an organic solvent in the art, such as propylene carbonate, ethylene carbonate, fluoroethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, methyl isopropyl carbonate, dipropyl carbonate, dibutyl carbonate, benzonitrile, acetonitrile, tetrahydrofuran, 2-methyltetrahydrofuran, γ-butyrolactone, dioxolane, 4-methyldioxolane, N,N-dimethylformamide, dimethylacetamide, dimethylsulfoxide, dioxane, 1,2-dimethoxyethane, sulfolane, dichloroethane, chlorobenzene, nitrobenzene, diethylene glycol, dimethyl ether, or a mixture thereof.
[0082] The lithium salt may be any lithium salt that can be used in the art. For example, LiPF 6 , LiBF 4 , LiSbF 6 , LiAsF 6 , LiClO 4 , LiCF 3 SO 3 , Li(CF 3 SO 2 ) 2 N, LiC 4 F 9 SO 3 , LiAlO 2 , LiAlCl 4 , LiN(C x F 2x+1 SO 2 )(C y F 2y+1 SO 2 ) (where x and y are natural numbers), LiCl, LiI, or a mixture thereof.
[0083] As can be seen from FIG. 4, the lithium battery 1 includes a positive electrode 3, a negative electrode 2, and a separator 4. The aforementioned positive electrode 3, negative electrode 2, and separator 4 are wound or folded and housed in a battery case 5. Next, an organic electrolyte is injected into the battery case 5, sealed with a cap assembly 6, and the lithium battery 1 is completed. The battery case can also be cylindrical, rectangular, thin film type, etc. For example, the lithium battery is also a thin film battery. The lithium battery is also a lithium ion battery.
[0084] A separator is disposed between the positive electrode and the negative electrode, and a battery structure can be formed. After the battery structure is laminated in a bicell structure, impregnated with an organic electrolyte, and the resulting product is housed and sealed in a pouch, a lithium ion polymer battery is completed.
[0085] Also, a plurality of the battery structures are laminated to form a battery pack, and such a battery pack can be used in all devices that require high capacity and high output. For example, it can be used in a notebook computer, a smartphone, an electric vehicle, etc.
[0086] In particular, since the lithium battery has excellent high rate characteristics and life characteristics, it is suitable for an electric vehicle (EV: electric vehicle). For example, it is suitable for a hybrid vehicle such as a plug-in hybrid electric vehicle (PHEV).
[0087] Furthermore, a method for manufacturing a porous composite according to still another embodiment includes supplying a reaction gas composed of a carbon source gas to silica or a first metal oxide and performing heat treatment, and preparing a composite precursor containing one or more selected from the silica or the first metal oxide and its reduction product SiO x (0 < x < 2) or a second metal oxide, and removing one or more selected from the silica or the first metal oxide and SiO x (0 < x < 2) or a second metal oxide from the composite precursor to prepare a porous composite.
[0088] The step of providing the composite precursor includes, for example, a step of supplying a reaction gas composed of a carbon source gas to a structure containing a metal oxide and performing heat treatment.
[0089] The step of providing the composite includes, for example, one or more first metal oxides represented by M a O c (0 < a ≤ 3, 0 < c ≤ 4, when a is 1, 2, or 3, b is an integer), supplying a reaction gas composed of a carbon source gas to the one or more first metal oxides and performing heat treatment, where M is one or more metals selected from Groups 2 to 13, Group 15, and Group 16 of the periodic table of the elements.
[0090] The carbon source gas is a compound represented by the following Chemical Formula 1, or a mixed gas of one or more selected from the group consisting of a compound represented by the following Chemical Formula 1; and a compound represented by the following Chemical Formula 2 and an oxygen-containing gas represented by the following Chemical Formula 3.
[0091] [Chemical Formula 1] C n H 2n+2-a [OH] a
[0092] In the above Chemical Formula 1, n is from 1 to 20, a is 0 or 1,
[0093] [Chemical Formula 2] C n H 2n
[0094] In the above Chemical Formula 2, n is from 2 to 6,
[0095] [Chemical Formula 3] C x H y O z
[0096] In the above Chemical Formula 3, x is 0, or an integer from 1 to 20, y is 0, or an integer from 1 to 20, and z is 1 or 2.
[0097] The compound represented by Chemical Formula 1 and the compound represented by Chemical Formula 2 are one or more selected from the group consisting of methane, ethane, propane, methanol, ethanol, and propanol. The oxygen-containing gas represented by Chemical Formula 3 is, for example, carbon dioxide (CO 2 ) and carbon monoxide (CO), water vapor (H 2 O), or a mixture thereof.
[0098] Silica and / or M a O c (0 < a ≤ 3, 0 < c ≤ 4, if a is 1, 2, or 3, then c is an integer), after the step of supplying a reaction gas composed of a carbon source gas to the first metal oxide and performing heat treatment, a cooling step using one or more inert gases selected from the group consisting of nitrogen, helium, and argon is further performed. The cooling step refers to the step of adjusting to room temperature (20 to 25°C). The carbon source gas also contains one or more inert gases selected from the group consisting of nitrogen, helium, and argon.
[0099] In the method for producing a composite precursor, the process of growing graphene by a gas-phase reaction is also carried out under various conditions.
[0100] According to the first condition, for example, methane is first supplied to a reactor in which a first metal oxide represented by silica and / or M a O c (0 < a ≤ 3, 0 < c ≤ 4, if a is 1, 2, or 3, then c is an integer) is arranged, and the temperature is raised to the heat treatment temperature (T). The temperature raising time to the heat treatment temperature (T) is 10 minutes to 4 hours, and the heat treatment temperature (T) is in the range of 700°C to 1,100°C. At the heat treatment temperature (T), heat treatment is carried out during the reaction time. The reaction time is, for example, 4 to 8 hours. The heat-treated product is cooled to room temperature to produce a composite. The time taken during the process of cooling from the heat treatment temperature (T) to room temperature is, for example, 1 to 5 hours.
[0101] According to the second condition, for example, silica and / or M a O c (0 < a ≤ 3, 0 < c ≤ 4, if a is 1, 2, or 3, then c is an integer) First, hydrogen is supplied to a reactor in which the first metal oxide represented by is arranged, and the temperature is raised to the heat treatment temperature (T). The temperature rising time to the heat treatment temperature (T) is 10 minutes to 4 hours, and the heat treatment temperature (T) is in the range of 700°C to 1,100°C. At the heat treatment temperature (T), after heat treatment for a certain reaction time, methane gas is supplied, and heat treatment is carried out during the remaining reaction time. The reaction time is, for example, 4 to 8 hours. The heat-treated product is cooled to room temperature to produce a composite. During the cooling process, nitrogen is supplied. The time taken for the process of cooling from the heat treatment temperature (T) to room temperature is, for example, 1 to 5 hours.
[0102] According to the third condition, for example, silica and / or M a O c (0 < a ≤ 3, 0 < c ≤ 4, if a is 1, 2, or 3, then c is an integer) First, hydrogen is supplied to a reactor in which the first metal oxide represented by is arranged, and the temperature is raised to the heat treatment temperature (T). The temperature rising time to the heat treatment temperature (T) is 10 minutes to 4 hours, and the heat treatment temperature (T) is in the range of 700°C to 1,100°C. At the heat treatment temperature (T), after heat treatment for a certain reaction time, a mixed gas of methane and hydrogen is supplied, and heat treatment is carried out during the remaining reaction time. The reaction time is, for example, 4 to 8 hours. The heat-treated product is cooled to room temperature to produce a composite. During the cooling process, nitrogen is supplied. The time taken for the process of cooling from the heat treatment temperature (T) to room temperature is, for example, 1 to 5 hours.
[0103] In the process of preparing the composite precursor, when the carbon source gas contains water vapor, a composite precursor having excellent conductivity can be obtained. The content of water vapor in the gas mixture is not limited, and is, for example, 0.01 to 10 vol% based on 100 vol% of the total carbon source gas. The carbon source gas is, for example, methane, a mixed gas containing methane and an inert gas, or a mixed gas containing methane and an oxygen-containing gas.
[0104] The carbon source gas can be, for example, methane, a mixture of methane and carbon dioxide, or a mixture of methane, carbon dioxide, and water vapor. In the mixture of methane and carbon dioxide, the molar ratio of methane to carbon dioxide is about 1:0.20 to 1:0.50, about 1:0.25 to 1:0.45, or about 1:0.30 to 1:0.40. In the mixture of methane, carbon dioxide, and water vapor, the molar ratio of methane to carbon dioxide and water vapor is about 1:0.20 to 0.50:0.01 to 1.45, about 1:0.25 to 0.45:0.10 to 1.35, or about 1:0.30 to 0.40:0.50 to 1.0.
[0105] The carbon source gas is, for example, carbon monoxide or carbon dioxide. The carbon source gas is, for example, a mixture of methane and nitrogen. In the mixture of methane and nitrogen, the molar ratio of methane to nitrogen is about 1:0.20 to 1:0.50, about 1:0.25 to 1:0.45, about 1:0.30 to 1:0.40. The carbon source gas does not include an inert gas such as nitrogen.
[0106] The heat treatment pressure can be selected in consideration of the heat treatment temperature, the composition of the gas mixture, and the amount of carbon coating desired. The heat treatment pressure can be controlled by adjusting the amount of the gas mixture flowing in and the amount of the gas mixture flowing out. The heat treatment pressure is, for example, 0.5 atm or more, 1 atm or more, 2 atm or more, 3 atm or more, 4 atm or more, or 5 atm or more.
[0107] The heat treatment time is not particularly limited and can be appropriately adjusted according to the heat treatment temperature, the pressure during heat treatment, the composition of the gas mixture, and the amount of the desired carbon coating. For example, the reaction time at the heat treatment temperature is, for example, from 10 minutes to 100 hours, from 30 minutes to 90 hours, or from 50 minutes to 40 hours. For example, the longer the heat treatment time, the more graphene (carbon) is deposited, whereby the electrical properties of the composite can be improved. However, such a tendency is not necessarily directly proportional to the time. For example, after a certain period of time, no more graphene deposition occurs, or the deposition rate becomes low.
[0108] Through the gas-phase reaction of the aforementioned carbon source gas, even at a relatively low temperature, silica (SiO 2 ) and / or M a O c (0 < a ≤ 3, 0 < c ≤ 4, if a is 1, 2 or 3, then c is an integer), and the first metal oxide represented by these and their reduction products, SiO x (0 < x < 2) and / or M a O b (0 < a ≤ 3, 0 < b < 4, a is 1, 2 or 3, and b is not an integer), a composite precursor is obtained by providing a uniform graphene coating on one or more selected from among the second metal oxides represented by these.
[0109] FIG. 3 is for explaining the formation process of a composite precursor according to an embodiment. It is not to be construed in a limited sense by the scale as shown in FIG. 3. FIG. 3 illustrates an embodiment.
[0110] Referring to FIG. 3, if a reaction gas composed of a carbon source gas is supplied to the upper part of the silica particles 10, graphene 11 will grow on the upper part of one or more 10a selected from among the silica particles and their reduction products. With the passage of the reaction time, silica and its reduction product (SiO xAbove 1 and up to 10b selected from (0 < x < 2), graphene 11 is gradually formed, and a composite precursor can be obtained.
[0111] The composite precursor may have a structure in which, for example, 1 or more up to 10c selected from silica particles and their reduction products are distributed on graphene 11. 1 or more up to 10c selected from silica particles and their reduction products are also distributed on graphene 11.
[0112] In FIG. 3, silica particles 10, 1 or more up to 10a selected from silica particles and their reduction products, and 1 or more up to 10c selected from silica particles and their reduction products are shown with different sizes, but this does not mean that they are limited to such sizes. In FIG. 3, the detailed structure of graphene is not illustrated in detail, but for example, graphene can also be of the film type or the nanosheet type, or a structure in which some flakes are mixed.
[0113] Regarding the definitions of the terms "nanosheet" and "membrane", they are as follows. The nanosheet indicates the case where graphene is formed irregularly on 1 or more selected from silica and its reduction products. The membrane refers to a film form in which graphene is continuously and uniformly formed on 1 or more selected from silica and its reduction products. The flake may correspond to the case where a part of the aforementioned nanosheet or membrane is damaged or deformed.
[0114] The composite precursor is, for example, a graphene matrix having 1 or more structures selected from a hemispherical structure, a spherical structure, a helical structure in which a plurality of hemispherical structures or spherical structures are connected, a cluster structure in which a plurality of hemispherical structures or spherical structures are aggregated, and a sponge structure, and M arranged within the graphene matrix a O b(0 < a ≤ 3, 0 < b ≤ 4, a is 1, 2, or 3, and b is an integer), and the first metal oxide represented by M a O c It contains one or more selected from the second metal oxides represented by (0 < a ≤ 3, 0 < c < 4, if a is 1, 2, or 3, then c is not an integer).
[0115] Next, a porous composite is prepared by removing one or more selected from the first metal oxide and the second metal oxide from the composite precursor.
[0116] The step of preparing the porous composite can also be carried out, for example, by dry etching or wet etching. The dry etching can be carried out by methods such as plasma, but it is not necessarily limited to such methods, and any method possible in the technical field is acceptable. The wet etching can also be carried out with an acid or a base. For example, after the porous composite is put into an acidic solution or a basic solution, it is stirred, and the first metal oxide and / or the second metal oxide can be dissolved and removed with an acid or a base. The acid that can be used includes, but is not limited to, hydrochloric acid, sulfuric acid, nitric acid, etc.
[0117] The step of preparing the porous composite may also include, for example, the step of putting the composite precursor into a basic solution and stirring it. The basic solution can be prepared by adding a base to distilled water. The base is, for example, LiOH, but is not limited thereto. The solvent is distilled water, but is not limited thereto, and alcohol, acetonitrile, etc. can be used.
[0118] The time for putting the composite precursor into the basic solution and stirring it is, for example, 5 to 200 hours, 10 to 200 hours, 50 to 200 hours, 80 to 100 hours, but is not limited to such a range.
[0119] The concentration of the acid or base contained in the acidic or basic solution is, for example, 0.1 to 10 wt %, or 1 to 5 wt %, but is not limited to such ranges.
[0120] The composite precursor is put into an acidic or basic solution, stirred, filtered to separate the residue, washed several times with distilled water to completely remove the acid or base, and then dried to obtain a porous composite.
[0121] Depending on the etching conditions, such as the concentration of the acidic or basic solution and the stirring time, the first metal oxide and / or the second metal oxide may be completely removed or may be partially left behind.
[0122] For example, by removing part or all of the silica particles 10, one or more selected from the silica particles and their reduction products 10a, and one or more selected from silica and its reduction products 10c in the composite precursor of Figure 3 through etching, a porous composite having nanopores arranged in the positions of the silica particles is obtained.
[0123] The present invention will be described in more detail with reference to the following examples and comparative examples. However, the examples are intended to illustrate the present invention and are not intended to limit the scope of the present invention.
[0124] (Production of graphene-silica composite) Production Example 1: Graphene Silica Composite Silica (SiO 2 ) particles (average particle size: about 15 nm, OCI) were placed in the reactor, and then CH 4 The temperature inside the reactor was raised to 1,000° C. under the conditions that about 300 sccm of 1 atm was supplied for about 30 minutes.
[0125] Next, the temperature was maintained for 7 hours to perform heat treatment. Next, the temperature inside the reactor was adjusted to room temperature (20 to 25°C) to separate silica particles and their reduction product, SiO xA composite (composite precursor) in which (0 < x < 2) particles are embedded in graphene was obtained.
[0126] (Manufacture of silicon-carbon composite negative electrode active material) Production Example 2: Production of silicon-carbon composite 25 parts by weight of plate-like and needle-like Si particles were mixed with 10 parts by weight of stearic acid and 65 parts by weight of isopropyl alcohol, and the composition was spray-dried and dried to obtain precursor secondary particles having an average particle size of about 4.5 μm. On the surface of silicon, silicon suboxide (SiO x )(0 < x < 2) was formed.
[0127] For the spray drying, a spray dryer (Model: MMSD Micro Mist Spray Dryers, manufactured by Fujisaki Electric Co., Ltd.) was used. Under a nitrogen atmosphere, the spray nozzle size and pressure were adjusted, the powder injection atmosphere temperature was adjusted to about 200 °C, and isopropyl alcohol was dried to produce precursor secondary particles.
[0128] After positioning the produced precursor secondary particles in the reactor, the internal temperature of the reactor was raised to 1,000 °C under the condition that a gas mixture of CH 4 :CO 2 = 80:20 volume ratio was supplied at about 300 sccm and 1 atm for about 30 minutes.
[0129] Next, heat treatment was performed by maintaining at the above temperature for 4 hours. Next, the internal temperature of the reactor was adjusted to room temperature (20 - 25 °C) to obtain porous silicon-carbon composite powder.
[0130] (Manufacture of porous composite) Example 1: Porous Composite 1 The graphene-silica composite synthesized in Production Example 1 was put into an aqueous solution of 3.2 wt% LiOH, stirred for 88 hours, and then the residue was filtered with a centrifuge.
[0131] The filtered residue was washed several times with distilled water to completely remove the base, and then dried to obtain a porous composite. The size of the nanopores contained in the porous composite was about 10 to 20 nm.
[0132] Example 2: Porous Composite 2 A porous composite was prepared in the same manner as in Example 1, except that the stirring time was changed to 6 hours.
[0133] (Manufacturing of lithium batteries (half-cell): Carbon-based anode) Example 3: Carbon-based negative electrode: Porous composite 1 (Manufacturing of carbon-based anodes) Natural graphite particles (manufactured by Mitsubishi Chemical), the powder of the porous composite 1 prepared in Example 1, styrene butadiene rubber (SBR) and carboxymethyl cellulose (CMC) were mixed in a weight ratio of 96:1:1.5:1.5, and then distilled water was added and stirred for 60 minutes using a mechanical stirrer to prepare a negative electrode active material slurry. The prepared negative electrode active material slurry was applied to a copper current collector having a thickness of about 60 μm using a doctor blade, dried at room temperature, dried in a hot air dryer at 100 ° C for 0.5 hours, and then dried once more under vacuum conditions at 120 ° C for 4 hours to prepare a negative electrode plate. The prepared negative electrode plate was roll pressed to prepare a negative electrode.
[0134] (Coin cell manufacturing) Using the negative electrode prepared above, lithium metal was used as the counter electrode, and a polypropylene separator (Cellguard 3510) was used. The mixture of ethylene carbonate (EC) + ethyl methyl carbonate (EMC) + diethyl carbonate (DMC) (volume ratio 2:4:4) was mixed with 1.15M LiPF as the lithium salt. 6 A coin cell was manufactured using the electrolyte to which the above was added.
[0135] Example 4: Carbon-based negative electrode: Porous composite 2 A negative electrode and a coin cell were manufactured in the same manner as in Example 3, except that the powder of the porous composite 2 prepared in Example 2 was used instead of the powder of the porous composite 1 prepared in Example 1.
[0136] Comparative Example 1: Graphene-Silica A negative electrode and a coin cell were prepared in the same manner as in Example 3, except that the graphene-silica composite powder prepared in Preparation Example 1 was used instead of the porous composite powder prepared in Example 1.
[0137] Comparative Example 2: Ketjen Black A negative electrode and a coin cell were manufactured in the same manner as in Example 3, except that Ketjen Black (EC600JD, Lion) was used instead of the porous composite powder manufactured in Example 1.
[0138] (Manufacturing of lithium batteries (half-cell): Silicon-carbon composite anode) Example 5: Silicon-carbon composite anode: Porous composite 1 (Manufacturing of silicon-carbon composite anode) The silicon-carbon composite powder prepared in Preparation Example 2, artificial graphite particles (particle size about 12 μm, manufactured by Shanshan), the powder of the porous composite 1 prepared in Example 1, and polyvinyl alcohol (PVA, manufactured by Aldrich) binder were mixed in a weight ratio of 18.5:76.5:1:4, and then distilled water was added and stirred for 60 minutes using a mechanical stirrer to prepare a negative electrode active material slurry. The prepared negative electrode active material slurry was applied to a copper current collector having a thickness of about 60 μm using a doctor blade, dried at room temperature, dried in a hot air dryer at 100 ° C for 0.5 hours, and then dried once more under vacuum conditions at 120 ° C for 4 hours to prepare a negative electrode plate. The prepared negative electrode plate was rolled to prepare a negative electrode.
[0139] (Coin cell manufacturing) Using the negative electrode prepared above, lithium metal was used as the counter electrode, and a polypropylene separator (Cellguard 3510) was used. 1.0M LiPF was used as the lithium salt in a mixed solvent of EC (ethylene carbonate) + DEC (diethyl carbonate) + FEC (fluorethylene carbonate) (volume ratio 5:70:25). 6 A coin cell was manufactured using the electrolyte to which the above was added.
[0140] Example 6: Silicon-carbon composite anode: Porous composite 1 A negative electrode and a coin cell were manufactured in the same manner as in Example 5, except that the content of the powder of the porous composite 1 prepared in Example 1 was changed to 0.5.
[0141] Comparative Example 3: Silicon-carbon composite anode: Ketjen black A negative electrode and a coin cell were manufactured in the same manner as in Example 5, except that Ketjen Black (EC600JD, Lion Co.) was used instead of the powder of the porous composite 1 manufactured in Example 1.
[0142] Evaluation example 1: XPS spectrum evaluation XPS spectra were measured for the porous composite 1 prepared in Example 1, the porous composite 2 prepared in Example 2, and the graphene-silica composite prepared in Preparation Example 1 using a Qunatum 2000 (Physical Electronics).
[0143] FIG. 2A shows peaks associated with the C 1s orbital, FIG. 2B shows peaks associated with the O 1s orbital, and FIG. 2C shows peaks associated with the Si 2p orbital.
[0144] As can be seen from FIG. 2A, in the composites of Example 1, Example 2 and Comparative Example 1, the magnitude of the carbon peak is shown to be high.
[0145] As can be seen from FIG. 2B, compared with the oxygen peak of the composite of Comparative Example 1, the oxygen peak of the porous composite of Example 2 was significantly reduced, and the oxygen peak of the carbon-based composite of Example 1 was negligible.
[0146] As can be seen from FIG. 2C, compared with the silicon peak of the composite of Comparative Example 1, the silicon peak of the porous composite of Example 2 was significantly reduced, and the silicon peak of the porous composite of Example 1 was almost absent.
[0147] The contents of silicon, oxygen and carbon calculated from the peak area are shown in Table 1 below.
[0148]
Table 1
[0149] As can be seen from Table 1 and FIGS. 2A to 2C, the porous composite of Example 1 has a negligible Si content of less than 0.5 at%, and most of the silica (SiO 2 ) particles and SiO x (0 <x <2) were removed by etching to form nanopores. In the porous composite of Example 2, about half of the silica (SiO 2 ) and SiO x (0 <x <2) were removed by etching to form nanopores.
[0150] Evaluation example 2: HR-TEM analysis High-resolution transmission electron microscope (HR-TEM) (Tecnai Titan (manufactured by FEI)) analysis was performed on the composite produced in Example 1.
[0151] FIG. 1A is an image of the graphene-silica composite before etching, and FIGS. 1B to 1E are images of the porous composite after etching.
[0152] As can be seen from FIG. 1A, the graphene-silica composite produced in Example 1 shows a structure in which silica (SiO 2 ) particles and SiO x (0 <x <2) particles reduced therefrom are embedded in graphene. Silica (SiO 2)It was confirmed that a graphene layer was disposed on the outer contour of one or more particles selected from particles and SiOx (0 < x < 2). Silica (SiO 2 ) particles and SiO x (0 < x < 2) among the selected one or more particles are uniformly dispersed in the graphene matrix. Silica (SiO 2 ) particles and SiO x (0 < x < 2) The particle size of one or more of the particles was about 15 nm. The particle size of the graphene-silica composite produced in Example 1 was about 100 nm to 200 nm. In FIG. 1A, the arrow indicates silica (SiO 2 ) particles and SiO x (0 < x < 2) one or more of the particles.
[0153] As can be seen from FIGS. 1B to 1E, in Example 1, in the porous composite produced by etching, silica (SiO 2 ) particles and SiO x (0 < x < 2) particles are hardly observed, and it shows that it has a structure in which nanopores are arranged in the graphene matrix. It was confirmed that a graphene layer was disposed on the outer contour of the nanopores. The nanopores are uniformly dispersed in the graphene matrix. The nanopores arranged in the graphene matrix are formed by removing silica (SiO 2 ) particles and SiO x (0 < x < 2) particles by etching. The particle size of the nanopores was about 15 nm. The particle size of the porous composite was about 100 nm to 200 nm.
[0154] Evaluation example 3: Room temperature charge / discharge characteristic evaluation: Carbon-based negative electrode active material The lithium batteries prepared in Example 3, Comparative Example 1, and Comparative Example 2 were charged at a constant current of 0.1C rate at 25°C until the voltage reached 0.01V (relative to Li), and then cut-off at a current of 0.01C0.05C rate while maintaining 0.01V in constant voltage mode. Next, the batteries were discharged at a constant current of 0.1C rate until the voltage reached 1.5V (relative to Li) (formation cycle).
[0155] The lithium battery that had undergone the chemical cycle was charged at a constant current of 0.1C rate at 25°C until the voltage reached 0.01V (for Li), and then discharged at a constant current of 0.1C rate until the voltage reached 1.5V (for Li) (first cycle). The lithium battery that had undergone the first cycle was charged at a constant current of 0.2C rate at 25°C until the voltage reached 0.01V (for Li). It was then discharged at a constant current of 0.2C rate until the voltage reached 1.5V (for Li) (second cycle). The lithium battery after the second cycle was charged at 25°C with a constant current of 0.5 C rate until the voltage reached 0.01 V (for Li). It was then discharged at a constant current of 0.2 C rate until the voltage reached 1.5 V (for Li) (third cycle). The lithium battery after the third initial cycle was charged at 25°C at a constant current of 1.0 C rate until the voltage reached 0.01 V (for Li). It was then discharged at a constant current of 0.2 C rate until the voltage reached 1.5 V (for Li) (fourth cycle). The lithium battery after the fourth cycle was charged at 25° C. with a constant current of 2.0 C rate until the voltage reached 0.01 V (relative to Li), and then discharged at a constant current of 0.2 C rate until the voltage reached 1.5 V (relative to Li) (fifth cycle).
[0156] In all charge / discharge cycles, a 10-minute rest period was allowed after each charge / discharge cycle. Some of the results of the room temperature charge / discharge experiments are shown in Table 2 below.
[0157] [Mathematical formula 1] Initial efficiency [%] = [discharge capacity at first cycle / charge capacity at first cycle] x 100
[0158] [Mathematical formula 2] High rate characteristic [%] = [C rate charge capacity (charge capacity at nth cycle) / 0.2C rate charge capacity (charge capacity at first cycle)] × 100
[0159] [Table 2]
[0160] As can be seen from Table 2, the lithium battery including the porous composite of Example 3 had improved initial efficiency and further improved high rate characteristics compared to the lithium battery including the graphene-silica composite of Comparative Example 1 and the lithium battery including the carbon-based conductive material of Comparative Example 2.
[0161] Evaluation example 4: Room temperature charge / discharge characteristic evaluation: silicon-carbon composite negative electrode active material The lithium batteries manufactured in Example 5, Example 6 and Comparative Example 3 were charged at a constant current of 0.1C rate at 25°C until the voltage reached 0.01V (relative to Li), and then cut off at a current of 0.01C rate while maintaining 0.01V in constant voltage mode. Next, the batteries were discharged at a constant current of 0.1C rate until the voltage reached 1.5V (relative to Li) (chemical formation cycle).
[0162] The lithium battery that had undergone the chemical formation cycle was charged at 25°C at a constant current rate of 0.2C until the voltage reached 0.01V (for Li), and then cut off at a current rate of 0.01C0.05C while maintaining 0.01V in constant voltage mode. Next, it was discharged at a constant current rate of 0.2C until the voltage reached 1.5V (for Li) (first cycle).
[0163] The lithium battery that had undergone the first cycle was charged at a constant current of 1C rate at 25°C until the voltage reached 0.01V (for Li), and then cut off at a current of 0.01C0.05C rate while maintaining 0.01V in constant voltage mode. Next, it was discharged at a constant current of 1C rate until the voltage reached 1.5V (for Li) (second cycle), and such cycles were repeated 50 times under the same conditions to measure the capacity retention rate.
[0164] In all charge / discharge cycles, a 10-minute rest period was allowed after each charge / discharge cycle. Some of the results of the room temperature charge / discharge experiments are shown in Table 3 below. The initial efficiency is expressed by the following mathematical formula 3, and the initial discharge capacity is the discharge capacity in the formation cycle.
[0165] [Mathematical formula 3] Initial efficiency [%] = [discharge capacity in formation cycle / charge capacity in formation cycle] x 100
[0166] [Table 3]
[0167] As can be seen from Table 3, the lithium battery including the porous composite of Example 5 had improved initial efficiency, discharge capacity and life characteristics compared to the lithium battery including the carbon-based conductive material of Comparative Example 3. The lithium battery including the porous composite of Example 6 had improved initial efficiency and the same level of discharge capacity compared to the lithium battery including the carbon-based conductive material of Comparative Example 3.
[0168] Although not shown in Table 3, the life characteristics of the lithium battery including the porous composite of Example 5 were at a similar level to that of the lithium battery including the carbon conductive material of Comparative Example 3. [Industrial Applicability]
[0169] By adopting a composite containing nanopores of 50 nm or less and graphene, the cycle characteristics of lithium batteries are improved. [Explanation of symbols]
[0170] 1 Lithium battery 2 negative electrode 3 Positive electrode 4. Separator 5 Battery case 6 Cap Assembly 10 Silica particles 11. Graphene
Claims
1. The nanopores and the graphene are included. The nanopores are disposed within a graphene matrix containing the graphene; The nanopores have a size of 1 to 40 nm and do not contain macropores of 50 nm or more. The porous composite is composed of silica and a reduction product of the silica, SiO x (0<x<2), and one or more metals selected from Groups 2 to 13, 15, and 16 of the Periodic Table of the Elements, and one or more oxides of the metals.
2. The graphene has a branched structure, the nanopores are distributed within the branched structure; 10. The porous composite of claim 1, wherein the branched structure comprises a plurality of graphene particles in contact with one another.
3. The graphene has a hemispherical or spherical structure; The porous composite of claim 1 , wherein the nanopores are distributed within the hemispherical structure or within the spherical structure.
4. 4. The porous composite of claim 3, wherein the size of the hemispherical structures is between 50 nm and 300 nm and the size of the spherical structures is between 50 nm and 300 nm.
5. The porous composite according to claim 1 , wherein the porous composite is a polyhedron / ball structure or a planar structure, and nanopores are distributed within the structure.
6. 2. The porous composite of claim 1, wherein the graphene comprises at least 1 to 20 graphene layers around the nanopores, and the graphene layer thickness is 0.6 to 12 nm.
7. The porous composite of claim 1 , wherein the nanopores have a size of 1 to 20 nm.
8. The silica or the SiO x 2. The porous composite of claim 1, wherein the content of silicon (Si) in (0<x<2) is 0.1 to 5 atomic %.
9. The metal oxide includes at least one selected from a first metal oxide and a second metal oxide that is a reduction product of the first metal oxide; The first metal oxide is represented by the formula M a O b (0<a≦3, 0<b≦4, and if a is 1, 2, or 3, then b is an integer), and the second metal oxide is one or more metals represented by the chemical formula M a O c (0<a≦3, 0<c<4, and if a is 1, 2, or 3, c is not an integer), 2. The porous composite according to claim 1, wherein the ratio b / a of a to b of the first metal oxide is greater than the ratio c / a of a to c of the second metal oxide, and M is at least one metal selected from Groups 2 to 13, 15, and 16 of the Periodic Table.
10. The first metal oxide is Al 2 O 3 , NbO, NbO 2 , Nb 2 O 5 , MgO, Sc 2 O 3 , TiO 2 , ZrO 2 , V 2 O 3 , W.O. 2 , MnO 2 , Fe 2 O 3 , Co 3 O 4 , PdO, CuO, AgO, ZnO, Sb 2 O 3 and SeO 2 and The second metal oxide is Al 2 O z (0<z<3), NbO x (0<x<2.5), MgO x (0<x<1), Sc 2 O z (0<z<3), TiO y (0<y<2), ZrO y (0<y<2), V 2 O z (0<z<3), WO y (0<y<2), MnO y (0<y<2), Fe 2 O z (0<z<3), Co 3 O w (0<w<4), PdO x (0<x<1), CuO x (0<x<1), AgO x (0<x<1), ZnO x (0<x<1), Sb 2 O z (0<z<3) and SeO y The porous composite according to claim 9 , wherein y is one or more selected from (0<y<2).
11. A negative electrode active material; A negative electrode comprising the porous composite according to claim 1 .
12. 12. The negative electrode according to claim 11, wherein the negative electrode active material comprises one or more metals selected from the group consisting of Si, Sn, Al, Ge, Pb, Zn, Ag, and Au, alloys thereof, oxides thereof, nitrides thereof, oxynitrides thereof, carbides thereof, or composites of these metals with a carbon-based material.
13. 12. The anode of claim 11, wherein the anode active material comprises one or more selected from the group consisting of silicon, silicon alloys, silicon nitrides, silicon oxynitrides, silicon carbides, and silicon-carbon composites.
14. The anode of claim 11 , wherein the anode active material comprises composite particles of silicon and carbon and a carbon-based coating layer disposed on the surfaces of the composite particles.
15. A positive electrode, a negative electrode, an electrolyte disposed between the positive electrode and the negative electrode; 11. A lithium battery, wherein one or more of the positive electrode and the negative electrode comprise the porous composite of claim 1 .
16. A reaction gas consisting of a carbon source gas is supplied to silica particles, and the silica and its reduction product, SiO x (0<x<2), From the composite precursor, the silica and SiO x and removing one or more selected from (0<x<2) to prepare a porous composite having nanopores arranged at the positions of the silica particles.
17. The method of claim 16, wherein the step of preparing the porous composite is performed by dry etching or wet etching.
18. The method of claim 17, wherein the wet etching is performed by an acid or a base.
19. The step of providing a porous composite includes: The method for producing a porous composite according to claim 16, comprising the step of stirring the composite precursor in a basic solution.
Citation Information
Patent Citations
Three-dimensionally ordered macroporous-mesoporous graphene, preparation method and application thereof
CN106554011A
Porous graphene material, its manufacturing method, and its application as an electrode material
JP2014507365A
Graphene material with randomly distributed two-dimensional structural defects
JP2014518835A
Porous carbon material and method of producing the same
JP2015164889A
Porous silicon-containing composite, carbon composite using the same, electrode, lithium battery, and electronic element including the same
JP2020066574A